Voucher TikTok Shop dan Influencer terhadap Keputusan Pembelian KFC melalui Perceived Value - Cristina (LPPM STIEM BONGAYA, 2026)
This study aims to analyze the influence of TikTok Shop voucher attractiveness and influencer on KFC purchase decisions among consumers in Pontianak City, with perceived value as a mediating variable. A quantitative approach was employed, with data collected from 151 respondents who were TikTok Shop voucher users in Pontianak City, selected through purposive sampling. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS software version 3.0. The results show that voucher attractiveness has a significant positive effect on perceived value but no significant direct effect on purchase decisions. In contrast, influencer has a significant positive effect on both perceived value and purchase decisions, while perceived value itself has a significant positive effect on purchase decisions. Perceived value fully mediates the effect of voucher attractiveness and partially mediates the effect of influencer on purchase decisions.